Современная рыночная электроэнергетика Российской Федерации - Бушуев С. А. Сергей Александрович; Виноградов К. А. Константин Анатольевич; Виноградов П. К. Павел Константинович; Гринкевич Е. Б. Егор Борисович; Громов Р. Е. Роман Евгеньевич; Гусева Е. Н. Екатерина Николаевна; Баркин О. Г. Олег Геннадьевич (Москва, Перо, 2017)
Авт. указ. на обороте тит. л.